Pengaruh CSR terhadap Nilai Perusahaan PT. Astra Internasional Tbk Periode 2017-2021 - Budi Dharma; Murni Sofiah; Elsa Zulfita (Transformasi: Journal of Economics and Business Management, 2022)
The Writing this article aims to analyze the effect of CSR (Corporate Social Responsibility) on the Company Value of PT. Astra Internasional Tbk in the 2017-2021 period. The research method used in this research is descrptive research method with a quantitative approach. The sampling technique used is purposive sampling with the sustainability report of PT. Astra Internasional Tbk for the 2017-2021 period as a sample. The analysis technique used is multiple linear regression. The results of the study show that CSR has no positive and significant influence on the company value (PBV) of Astra Internatonal Tbk in 2017-2021, because maybe the investors compare Astra’s finansial rations more than looking at it’s CSR reports